Inovasi Media Pembelajaran Pendidikan Ekonomi Berbasis Kecerdasan Buatan Terintegrasi (Integreted Artificial Intelegence) dengan Ubiquitous Learning - Achmad Murdiono; Andi Basuki; Andreas Syah Pahlevi; Nik Mohd Hazrul Nik Hashim (Jurnal Pendidikan Ekonomi, 2021)
Human Resource Development (HR) is part of the process and objectives of Indonesia's economic development. Therefore, strategic steps are needed in realizing education as one of the pillars in realizing quality human resources. The purpose of this research is to design and build innovative learning media that is integrated with ubiquitos learning through artificial intelligence technology by utilizing Chatbot application features that can be used. for learning economic education. This research consists of three main stages, namely (1). Preliminary study by conducting theoretical and field agreements so as to be able to formulate needs in the preparation of the platform. (2). The second stage begins with product planning by providing product differentiation in the form of chatbots and daily intensive courses which then develops into a Learning Management System in the initial form of the product. (3). The activity required at this stage is the first trial by experts to validate the material and media. The results of this study are in the form of a platform developed in the form of text, animation, and video by utilizing artificial intelligence (AI) technology on chatbot application features that are tailored to the needs and stages of student learning in economics subjects that have been implemented in the Integrated Learning Management System. DOI: https://dx.doi.org/10.17977/UM014v14i22021p179